Research Progress on Animal Models of Sepsis-Related Organ Injury - YANG Jiahao; DING Chunlei; QIAN Fenghua; SUN Qi; JIANG Xusheng; CHEN Wen; SHEN Mengwen (Shiyan dongwu yu bijiao yixue)
Sepsis is a multi-organ dysfunction syndrome caused by infection and immune dysfunction, with a high mortality rate. It affects multiple important organs such as the heart, lungs, kidneys, liver, and brain. Establishing corresponding animal models of organ dysfunction syndrome is an essential step in clarifying its pathogenesis, researching potential effective drugs, and evaluating the effectiveness and safety of treatment plans. This article first summarizes classic modeling methods for sepsis related organ injury, including the destruction of intestinal barrier tissue integrity and the implantation of pathogens or toxic drugs. The former mainly includes cecal ligation and puncture, ascending colon stent implantation, and cecal ligation incision. The latter is divided into intraperitoneal injection, intravenous injection, and intratracheal administration based on the clinical infection route being simulated. Cecal ligation and puncture and lipopolysaccharide intraperitoneal injection are the most commonly used methods. Secondly, this article summarizes the common modeling methods and evaluation methods for animal models of sepsis-induced cardiomyopathy, acute lung injury, acute kidney injury, acute liver injury, and brain dysfunction. It points out that almost all organ injuries use classic modeling methods, and different organ injury models have additional modifications according to their different pathogenesis. For example, in addition to the classic modeling methods, lipopolysaccharide instillation in the trachea is more effective in modeling acute lung injury as it better simulates lung barrier dysfunction. Cecal ligation and puncture followed by Pseudomonas instillation in the trachea in a secondary challenge model better represents sepsis-induced acute kidney injury. Intraperitoneal injection of galactosamine is a mature modeling method of sepsis-induced acute liver injury. Intracerebral injection of lipopolysaccharide is a feasible model of sepsis-associated encephalopathy. In addition to the different modeling methods, there are differences in the administration time, dosage and experimental time points according to the different experimental purposes. This article reviews the research progress of animal experimental models for sepsis-induced cardiomyopathy, acute lung injury, acute kidney injury, acute liver injury, and brain dysfunction, aiming to provide a reference for the selection of animal experimental models and optimization of experimental design.